Koncepcje eugeniczne w polskiej nauce kryminologii w okresie międzywojennym (aspekty prawno-kryminalne) - Koredczuk, Józef (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The aim of the article is to show the role of eugenic concepts in the views of Polish legal criminologists looking for solutions to reduce crime. One way they considered was castration and especially sterilization of criminals, believing that the propensity to commit crimes is hereditary. These concepts raised great moral and ethical doubts as well as legal ones. Most of them met with opposition from Polish lawyers, but were still popular due to the inﬂuence of the anthropological school in the study of criminal law. In the 1930s, the solutions were adopted in German law.
Keywords: eugenika; kryminologia; okres międzywojenny; prawo karne; przestępczość; sterylizacja